The influence of personality factors in the adolescent-parent relationship - Sandu, Mihaela Luminita; Rus, Mihaela; Tasente, Tanase; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2020)
Constituting the oldest of man-made institutions throughout its social-historical existence, the family is a form of human communication whose relationships between its members, of natural-biological, spiritual-affective and moral-legal essence, allow the continuity of the species and the evolution of society. Various studies and research have shown that the development of the child's personality can be achieved only within the family matrix, both educational models and the emotional and instrumental qualities of the family environment create strong premises for the harmonious evolution of the child, to which parents have a fundamental responsibility.The physiology of the child can be deeply marked by the way in which the parents respond to his needs for food, protection, affection and care, just as the development of his skills and attitudes can only be done in the presence of both parents. If one of them is absent from the home or there are conflicts between the parents, the child will develop contradictory tendencies and norms that will prevent his proper evolution.